The Model Disclosure of Islamic Social Reporting in Islamic Bank Indonesia - Indra Siswanti; Embun Prowanta (Universitas Mercu Buana, 2022)
Objectives: The purpose of this study is to analyze the determinants of the disclosure of Islamic Social Reporting in Islamic banks in IndonesiaMethodology: The population in this study are Islamic banks in Indonesia which amounted to 14 (fourteen) in total, while the sample used was 9 (nine) Islamic banks that have met the criteria, namely Islamic banks that have published financial reports, annual reports and corporate governance reports between the period of period 2015-2019.Finding: The results of this study indicate that compliance with sharia principles, duties and responsibilities of the sharia supervisory board have a significant positive effect on the disclosure of ISR whereas financial performance has no effect on the disclosure of ISR. Corporate governance has shown moderate effect of compliance sharia on the disclosure of ISR, while Corporate governance does not moderate effect of duties and responsibilities of sharia supervisory board on disclosure of ISR and Corporate governance moderate effect of financial performance on the disclosure of ISR.Conclusion: It is important for the Islamic banks in Indonesia to maintain compliance sharia principles, and to increase the role of sharia supervisory boards, financial performance and the implementation of corporate governance.